Analiza porównawcza mechanizmów psychologicznej adaptacji osobowości w warunkach ograniczonych możliwości fizycznych = Comparative analysis of the mechanisms of psychological adaptation of personality in terms of physical disability - Bogomaz, Sergei L.; Paškovič, Sergei F. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article analyzes the mechanisms of psychological adaptation of personality in terms of physical disability caused by damage to the musculoskeletal system. The study found that conditions for successful psychological adaptation is not the creation of comfortable conditions of existence and the desire for independence and maximize available resources.
Keywords: adaptacja psychologiczna; coping - strategie; mechanizmy obrony psychologicznej; ludzie z uszkodzeniem układu mięśniowo-szkieletowego; psychological adaptation; coping strategies; psychological defense mechanisms; people with damage to the musculoskeletal system